High Incidence of Herpes Zoster After Cord Blood Hematopoietic Cell Transplant Despite Longer Duration of Antiviral Prophylaxis. (9th March 2020) - Xue, Elisabetta; Xie, Hu; Leisenring, Wendy M; Kimball, Louise E; Goyal, Sonia; Chung, Lisa; Blazevic, Rachel; Maltez, Byron; Edwards, Anna; Dahlberg, Ann E; Salit, Rachel B; Delaney, Colleen; et al.
Abstract: Background: Cord blood transplant (CBT) recipients have a high incidence of herpes zoster (HZ) in the context of short-term peritransplant antiviral prophylaxis. In 2009, international guidelines recommended HZ prophylaxis for at least 1 year after hematopoietic cell transplant. The impact of longer-term antiviral prophylaxis on HZ incidence after CBT is unknown. Methods: We retrospectively analyzed varicella zoster virus (VZV)–seropositive CBT recipients who were transplanted between 2006 and 2016. We abstracted HZ events and other variables for up to 5 years post-CBT. We calculated the cumulative incidence of HZ and used Cox proportional hazards regression to identify variables associated with HZ. Results: The study cohort consisted of 227 patients. Among 1-year survivors, 91% were still receiving prophylaxis, for a median duration of 20.6 months. HZ occurred in 44 patients (19%) at a median of 23.6 months. The cumulative incidence of HZ by 1 year after CBT was 1.8% (95% confidence interval [CI], .1%–4%), but increased to 26% (95% CI, 19%–33%) by 5 years. In a multivariable analysis, acute graft-vs-host disease was associated with increased risk, whereas antiviral prophylaxis was associated with reduced risk for HZ (adjusted hazard ratio, 0.19 [95% CI, .09–.4]). There was no association between CD4 + T-cell counts at 1 year post-CBT and subsequent risk for HZ. Conclusions: We found a high incidence of HZ after CBT despite antiviral prophylaxis for > 1 year. Based on these findings, we suggest longer duration of prophylaxis for HZ after CBT. Compliance with antiviral prophylaxis, VZV-specific immune monitoring, and vaccination to mitigate HZ after CBT also require further study. Abstract : Cord blood transplant (CBT) recipients have a high cumulative incidence of herpes zoster (HZ) despite longer-term antiviral prophylaxis. Antiviral prophylaxis during immunosuppression and for 3 or more years might reduce the incidence and complications of HZ after CBT.